GROUP PLAY THERAPY TO INCREASE SOCIAL CONNECTEDNESS IN THE ELDERLY AT PELKRIS ELIM NURSING HOME SEMARANG - Joshua Massie; Siswanto; Erna Agustina Yudiati (RADJA PUBLIKA, 2025)
This study aims to test the effectiveness of Group Play Therapy in increasing the social connectedness of the elderly at Pelkris Elim Nursing Home, Semarang. The study used a mixed-methods approach involving 12 elderly individuals (N=12) in a short-term intervention of 4 sessions. Quantitative data were measured using the Social Connectedness Scale-Revised (SCS-R) at pre-test and post-test and analyzed with a Paired-Samples T-Test, while qualitative data were explored through the dynamics of changes in the elderly's connectedness during the Group Play Therapy process. Quantitatively, Group Play Therapy was effective in increasing social connectedness. The participants' average score increased from pre-test (M = 45.67, SD = 14.61) to post-test (M = 70.33, SD = 15.70). The Paired-Samples T-Test results confirmed that this difference was highly significant (t(11) = -8.527, p < .001). A clinically meaningful impact was also evident, where the group's average score successfully shifted to the 'socially connected' category (mean item score = 3.52), and 9 out of 12 participants who were initially disconnected successfully reached this category. Qualitatively, this intervention successfully facilitated group dynamics that supported the development of friendship, affiliation, and connectedness aspects.